Project method in activities of adopting mathematical concepts - Janković, Branka B (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
The project method in the activities of adopting mathematical concepts can be used to solve a variety of mathematical problems arising from the real world. This method requires the team work of children and educators, as well as their additional engagement in the implementation of the project. In this case, educators face additional challenges such as deviation from the usual teaching methods, additional engagement in the study of the real problem and academic literature, unexpected situations during the project development and the uncertainty of the results of the project. The paper presents the phases of the project implementation, as well as one example of the adoption of mathematical concepts through the project. Recommendations have been given given for project themes that can be processed by the project method in the activities of adopting mathematical concepts.